Carnian beds at Tamar and at Log pod Mangartom - Ogorelec, Bojan; Jurkovšek, Bogdan; Šribar, Ljudmila; Jelen, Bogomir; Stojanovič, Božo; Mišič, Miha (Geologija, 1984)
Investigated were Carnian beds in Tamar and at Log pod Mangartom. In the paper are presented results of microfacial, paleontological, mineralogical and geochemical analyses. The Cordevolian dolomite is of light color, and it contains above 90 % carbonate. It was formed by early and late diagenetic dolomitization of biomicritic and stromatolitic limestone in the littoral and sublittoral environment of the open shelf. Julian-Tuvalian beds are of dark color. They are characterized by interbedding of layered marlv limestone with thinner sheets of marl and shale. Limestone is biomicritic and it contains numerous pelecypods and foraminifers. It was deposited in a very shallow restricted shelf with lagoons (reducing environment). Carbonate deposition was at times interrupted by supply of detritic component. Julian-Tuvalian beds are overlain by layered dolomite which passes upwards into the Dachstein limestone. Microfacial analyses of Julian-Tuvalian beds indicate at Tamar and at Log pod Mangartom a rather uniform and monotonous development, respectively a similar depositional environment. The term Tamar Formation can therefore be extended also to carbonate clastic beds in the surroundings of Log pod Mangartom.